2021
DOI: 10.51201/jusst/21/05164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Osseo densification burs and osteotome technique for closed sinus lift in partially edentulous maxilla (clinical and radiological study)

Abstract: Dental implants are considered the first choice to replace lost or non-restorable teeth. However, the posterior maxilla remains a challenge in its management because of the quality of bone in the posterior maxilla. Osseo densification (OD) concept has been proposed in the literature to improve primary implant stability, which is an important aspect of osseointegration. Densah bur is novel drills specially designed to enhance a bone density by Osseo densification, which in turn increases primary stability. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
0
1
Order By: Relevance
“…However, our finding contradicts other studies that reported no significant difference concerning primary stability between the Densah and osteotome techniques [32,33]. Secondary stability measured after 6 months shows a statistically significant difference in the mean implant stability measurements among the three groups; again, Densah has the highest mean implant stability, which is in agreement with previous results [32,34]. On the other hand, the results were also compared with those of another study [24,33], which reported no statistically significant difference between the piezosurgery and osteotome techniques; both showed lower mean implant stability measurements that were statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our finding contradicts other studies that reported no significant difference concerning primary stability between the Densah and osteotome techniques [32,33]. Secondary stability measured after 6 months shows a statistically significant difference in the mean implant stability measurements among the three groups; again, Densah has the highest mean implant stability, which is in agreement with previous results [32,34]. On the other hand, the results were also compared with those of another study [24,33], which reported no statistically significant difference between the piezosurgery and osteotome techniques; both showed lower mean implant stability measurements that were statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is similar to those of other studies [30,31] that demonstrated the highest implant stability to characterize the Densah group. However, our finding contradicts other studies that reported no significant difference concerning primary stability between the Densah and osteotome techniques [32,33]. Secondary stability measured after 6 months shows a statistically significant difference in the mean implant stability measurements among the three groups; again, Densah has the highest mean implant stability, which is in agreement with previous results [32,34].…”
Section: Discussionsupporting
confidence: 64%